Dynamic Adhesion Assay for the Functional Analysis of Anti-adhesion Therapies in Inflammatory Bowel Disease - Becker, Elisabeth; Schramm, Simon; Binder, Marie-Theres; Allner, Clarissa; Wiendl, Maximilian; Neufert, Clemens; Atreya, Imke; Neurath, Markus; Zundler, Sebastian (Journal of Visualized Experiments, 2018)
Gut homing of immune cells is important for the pathogenesis of inflammatory bowel diseases (IBD). Integrin-dependent cell adhesion to addressins is a crucial step in this process and therapeutic strategies interfering with adhesion have been successfully established. The anti-α4β7 integrin antibody, vedolizumab, is used for the clinical treatment of Crohn's disease (CD) and ulcerative colitis (UC) and further compounds are likely to follow. The details of the adhesion procedure and the action mechanisms of anti-integrin antibodies are still unclear in many regards due to the limited available techniques for the functional research in this field. Here, we present a dynamic adhesion assay for the functional analysis of human cell adhesion under flow conditions and the impact of anti-integrin therapies in the context of IBD. It is based on the perfusion of primary human cells through addressin-coated ultrathin glass capillaries with real-time microscopic analysis. The assay offers a variety of opportunities for refinements and modifications and holds potentials for mechanistic discoveries and translational applications.
EVALuna2:207768